2017
DOI: 10.1073/pnas.1709120114
|View full text |Cite|
|
Sign up to set email alerts
|

TFG facilitates outer coat disassembly on COPII transport carriers to promote tethering and fusion with ER–Golgi intermediate compartments

Abstract: The conserved coat protein complex II (COPII) mediates the initial steps of secretory protein trafficking by assembling onto subdomains of the endoplasmic reticulum (ER) in two layers to generate cargo-laden transport carriers that ultimately fuse with an adjacent ER–Golgi intermediate compartment (ERGIC). Here, we demonstrate that Trk-fused gene (TFG) binds directly to the inner layer of the COPII coat. Specifically, the TFG C terminus interacts with Sec23 through a shared interface with the outer COPII coat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
99
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 94 publications
7
99
0
1
Order By: Relevance
“…Strikingly, depletion of TFG not only results in the stabilization of COPII‐coated transport carriers, but also their aberrant appearance away from the ER/ERGIC interface, suggesting an additional role for TFG in tethering COPII carriers prior to full uncoating and fusion with ERGIC membranes . Consistent with this idea, recombinant TFG is sufficient to cluster inner COPII‐coated liposomes in vitro . In particular, the carboxyl‐terminal intrinsically disordered domain of TFG is critical for this activity.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Strikingly, depletion of TFG not only results in the stabilization of COPII‐coated transport carriers, but also their aberrant appearance away from the ER/ERGIC interface, suggesting an additional role for TFG in tethering COPII carriers prior to full uncoating and fusion with ERGIC membranes . Consistent with this idea, recombinant TFG is sufficient to cluster inner COPII‐coated liposomes in vitro . In particular, the carboxyl‐terminal intrinsically disordered domain of TFG is critical for this activity.…”
Section: Introductionmentioning
confidence: 70%
“…In particular, the carboxyl‐terminal intrinsically disordered domain of TFG is critical for this activity. Previous work suggested that this region of TFG is capable of self‐assembly into larger structures (≈200–300 nm in size), raising the possibility that elevated concentrations of TFG can lead to phase separation within the cytoplasm, potentially forming a membrane‐less liquid droplet . By generating a phase separated liquid droplet at the interface between ER and ERGIC membranes, COPII transport carriers may become transiently trapped, providing sufficient time for the inner coat to disassociate (Figure ).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations